Hukuman Bagi Pencuri (Studi Komparatif Antara Madzhab Syafi’i Dan Madzhab Az-Zahiri) - Nur Hikmah Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to find out the punishment for thieves according to the Syafi'i school of thought. And to find out the punishment for thieves according to az-Zahiri. And to know the differences and similarities between madzhab opinions. This research was carried out using library research and paying attention to the field (Field Research). Literature study is a process of searching for various literature, the results of studies related to the research to be carried out. The results of the research show that the punishment for thieves in the Syafi'i school of thought is cutting off their hands. If the thief has been charged by the law (mukallaf), not under duress, the thing stolen is not an item of doubt, and the theft did not occur during a war in the way of Allah. Likewise, stolen goods are taken secretly or secretly, the thing taken is property, the property belongs to/belongs to someone else, and the stolen property reaches the nisab. With a minimum limit on the price of the stolen goods, it is a quarter of a dinar, and simplified to Rp. 812,500,-. The similarity between the Shafi'i and az-Zahiri schools of thought is that the punishment for thieves is cutting off their hands. And the legal basis for theft is Surah al-Maidah verse 38. Meanwhile, the difference is in the nominal amount of the item stolen and the location of the item stolen. The Syafi'i Madzhab requires that the minimum price for stolen goods be a quarter of a dinar. If it is less than that then you will be subject to ta'jir. Meanwhile, az-Zahiri did not question the nisab of these goods because of the generality of the verse. And according to the as-Safi'i school of thought, the goods must be in a special place, while az-Zahiri does not have to place the goods in a prepared place.